2018
DOI: 10.1111/jog.13846
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab mitigates ovarian ischemia–reperfusion injury in rats by regulating oxidative stress, apoptosis and resolution of inflammation

Abstract: Aim: Ovarian torsion is a rare but an important reason of acute lower abdominal pain in women and associated with serious morbidity and mortality, if not treated promptly. The aim of this study was to evaluate the effects of an antitumor necrosis factor-α antibody on ovarian torsion in a rat model of ischemiareperfusion (I/R) injury. Methods: Forty female Wistar Albino rats were used in the present study. The rats were randomly divided into four groups: group I (sham), group II (I/R), group III (I/R + isotonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…In our study, it was observed that NF‐κB expression increased in the ovarian tissue following I/R compared to the healthy group. This result is consistent with previous ovarian I/R studies 13,45 . In addition, in our study, a dose‐dependent decrease in NF‐κB expression was observed in the groups receiving GOS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, it was observed that NF‐κB expression increased in the ovarian tissue following I/R compared to the healthy group. This result is consistent with previous ovarian I/R studies 13,45 . In addition, in our study, a dose‐dependent decrease in NF‐κB expression was observed in the groups receiving GOS.…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with previous ovarian I/R studies. 13,45 In addition, in our study, a dose-dependent decrease in NF-κB expression was observed in the groups receiving GOS. This result is in agreement with Cinar et al who reported that the application of GOS decreased elevated NF-κB expression after sepsis-induced injury.…”
Section: Discussionsupporting
confidence: 65%
“…Cat No: 84029) antibodies. Light microscopic (Olympus CX43) evaluation of immunohistochemically stained sections was Scored as described previously in the literature as 0, no staining; 1, weak but detectable staining; 2, moderate staining; and 3, strong staining [17].…”
Section: Immunohistochemical Evalutionmentioning
confidence: 99%
“…When published literature was evaluated, the protective effects of many agents against I‐ and I/R‐related damage to the ovarian tissue as a result of ovarian torsion have been demonstrated histopathologically or with serum biochemical markers 8,12,13 . The protective effect of PRP on ovarian torsion has been shown in previous studies in the context of histopathology and serum biochemical markers 14 .…”
Section: Introductionmentioning
confidence: 96%